MOA-2020-BLG-135Lb: a new Neptune-class planet for the extended MOA-II exoplanet microlens statistical analysis - Silva, Stela Ishitani; Ranc, Clément; Bennett, David P.; Bond, Ian A.; Zang, Weicheng; Abe, Fumio; Barry, Richard K.; Bhattacharya, Aparna; Fujii, Hirosane; Fukui, Akihiko; Hirao, Yuki; Itow, Yoshitaka; et al. (The astronomical journal, 2022)
We report the light-curve analysis for the event MOA-2020-BLG-135, which leads to the discovery of a new Neptune-class planet, MOA-2020-BLG-135Lb. With a derived mass ratio of and separation s ≈ 1, the planet lies exactly at the break and likely peak of the exoplanet mass-ratio function derived by the Microlensing Observations in Astrophysics (MOA) Collaboration. We estimate the properties of the lens system based on a Galactic model and considering two different Bayesian priors: one assuming that all stars have an equal planet-hosting probability and the other that planets are more likely to orbit more-massive stars. With a uniform host mass prior, we predict that the lens system is likely to be a planet of mass and a host star of mass , located at a distance . With a prior that holds that planet occurrence scales in proportion to the host-star mass, the estimated lens system properties are , , and . This planet qualifies for inclusion in the extended MOA-II exoplanet microlens sample.
Gesehen am 16.11.2022